Input hypotheses for developing EFL/ESL learners’ listening comprehension skills - Kasimo, Yulius Yosef; Ota, Maria Kristina; Kara, Yuliana M. D’Karmel (Univeritas Papua, 2024)
The objective of this study is to examine the significance of the input hypothesis in enhancing the listening comprehension abilities of EFL/ESL learners. The methodology employed in this study is a critical literature review. This entailed a comprehensive search for relevant articles and other sources, a meticulous reading of the material, the categorization of data, a thorough analysis, and the synthesis of findings. The findings of this study indicate that the input hypothesis plays an essential role in developing ESL/EFL learners' listening comprehension abilities through the acquisition of comprehensible inputs. The activation of linguistic background knowledge enables EFL/ESL learners to develop pronunciation skills, understanding of grammatical accuracy, lexical resources, and meaning. Optimizing the inputs of the listening strategy (cognitive, metacognitive, socio-affective) assists EFL/ESL learners in activating their memory about listening materials. This is achieved through making inferences, elaborations, summaries, translations, observations, assessments, and becoming involved in the community. Inputs from media, audio (visual), and practices can develop EFL/ESL learners' cognition, motivation, stimulating perception, activating prior knowledge. In conclusion, the components of the comprehensible inputs must be integrated and developed in a coordinated manner during the teaching and learning process of listening skills.